2009
DOI: 10.5194/acpd-9-23695-2009
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Technical Note: Detection and identification of radical species formed from α-pinene/ozone reaction using DMPO spin trap

Abstract: The reactions of ozone with monoterpenes proceed via the formation of multiple oxygen-and carbon-centered free radical species. These radical species are highly reactive and thus, have generally not been measureable. A method for their detection and characterization is needed to preserve these radicals for a sufficiently 5 long time to permit analyzes to be performed. Radical-addition reactions, also called spin trapping techniques, allow the detection of short-lived radicals. This approach has been applied to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…In many articles, it has been speculated that photohydroxylation of aromatic compounds in aqueous solution is initiated by light excitation and the generation of aryl radicals, based on indirect experimental results. , Significantly, however, the previously reported mechanisms of OH-PBDEs formation, based on calculation results and final products from gas-phase experiments, did not provide direct evidence for the formation of reactive aryl radicals. , To completely explain the process of the photoformation of OH-PBDEs, we sought to identify reactive aryl radicals by using DMPO as an effective trapping agent for carbon-centered radical species …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In many articles, it has been speculated that photohydroxylation of aromatic compounds in aqueous solution is initiated by light excitation and the generation of aryl radicals, based on indirect experimental results. , Significantly, however, the previously reported mechanisms of OH-PBDEs formation, based on calculation results and final products from gas-phase experiments, did not provide direct evidence for the formation of reactive aryl radicals. , To completely explain the process of the photoformation of OH-PBDEs, we sought to identify reactive aryl radicals by using DMPO as an effective trapping agent for carbon-centered radical species …”
Section: Resultsmentioning
confidence: 99%
“…The reaction solutions were extracted by means of solid-phase extraction (SPE) cartridges (C 18 , 500 mg, 6 cc, Waters) and the extractives were detected by high performance liquid chromatography (HPLC, Waters 2695, photodiode array detector (PDA) 2996, Waters, USA). Subsequently, the sample from BDE-47 photolysis with DMPO and Fe­(III) in acetonitrile/water (AcCN/water) solution was identified by means of an Agilent 1200 Series HPLC-electrospray ionization-triple quadrupole 6410 mass spectrometer (LC-ESI-MS/MS, Agilent) operating in negative ion mode. , In order to obtain satisfactory signals from tetra-BDE-DMPO, the experiment was carried out using acetonitrile as a cosolvent (AcCN/water = 6:4) under nitrogen-saturated conditions. AcCN is considered to be an effective cosolvent that does not have any obvious impact on the reactive intermediates produced by the photolysis of PBDEs or the chromatographic detection.…”
Section: Methodsmentioning
confidence: 99%
“…[18][19][20] The NP from the lanthanide series generated by spray flame synthesis offers unique advantageous properties such as magnetic phosphorescence, and due to their extreme low natural background signal, can be detected by ICP-MS with high sensitivity. In a recent proof-of-concept study 21 with Eu and Gd NPs, it was confirmed that 24 hours after intratracheal delivery, the majority (59%) of the dose remained in the lungs, with a cleared fraction of 20% found in the feces and only 0.2% detected in the liver or even less for other secondary organs.…”
Section: Dosimetry and Environmental Fate Of Pollutants From Combustion Sources (Tobias Stöger)mentioning
confidence: 89%
“…α -pinene) with ozone, which is important for understanding the health effects associated with the ambient particulate mass. Previous studies have shown that a significant amount of reactive oxygen species, during the reaction of α-pinene with ozone, are associated with secondary organic aerosols (SOA) 21 . Mechanisms of free radical formation are important to understand since health effects have been associated with radical-containing PM; and SOAs can have direct and indirect effects on climate change.…”
Section: Dosimetry and Environmental Fate Of Pollutants From Combustimentioning
confidence: 99%
“…The low aqueous solubility (about 2.5 mg/L at 25 • C), high photosensitivity, and high volatility restrict the application of α-pinene [13][14][15]. The development of encapsulation systems loading α-pinene can be utilized to improve the physicochemical properties of the compound and to allow its controlled release from the fabricated matrices [16].…”
Section: Introductionmentioning
confidence: 99%